Exegesis of the Holy Qur’an as Legal Framework of Muslim Patients’ Rights in the Contemporary Muslim Societies - Ahmed Abiodun Muhammed-Mikaaeel; Abdul-Qadir Zubair; Abdulsalam Lukman Oladele (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background and Objectives: Muslims in non-Islamic states continuously face lots of challenges regarding recognition and observance of the Muslim patients’ rights (MPRs). There is widespread misconception that Islamic law does not explicitly cover patients’ rights. Methodology: The study adopts doctrinal method of Islamic legal research exploring foundation of the MPRs from the Holy Qur’an. Qur’anic exegesis explores Tafseer of Al-Qurtubi and As-Sa’di which are based on Ayat al-Ahkam (legislative verses). Relevant secondary sources of information were explored at academia, google scholar, google search engine, research gate, sage-pub, semantic, Brill, and jostor. The main results: The study finds that the MPRs emanated from the relevant verses of the Holy Qur’an especially the Qur’an Chapter 24 verse 30-31 and Quran Chapter 33 verse 59. The MPRs include same-gender treatment, presence of mahram during medical treatment, privacy and coverage of ‘awrah, separate hospital wards for different genders etc. Though the MPRS are very sacrosanct; they are not absolute and relaxable under emergencies to save life in compliance with certain cautions. This research contribution: The existing literature focused on medical fatwas and thematic interpretations with dearth of Qura’nic interpretative literature of modern healthcare regarding MPRs. The study fills the gap by coming up with up a model of legal framework, mapping table of verses and policy recommendations for the contemporary Muslim societies. Conclusion: The study finds that the MPRs are inherently inalienable having emanated from Holy Qur’an. The study recommends pragmatic integration of Islamic etiquettes in hospital policies and medical principles for the recognition of the MPRs